Operation mechanism for ensuring the stable migration of top-level domain name resolution hosting services with DNSSEC - Zheng HE; Feng LENG; Cuiling ZHANG (网络与信息安全学报)
Based on the migration and deployment practice of the top-level domain resolution service hosting platform, in order to avoid the occurrence of domain name system security extension (DNSSEC, DNS security ex-tension) trust chain and resolution service interruption, domain name NS record inconsistency and other security issues in the DNSSEC environment, research and analysis was focused on how to migrate the resolution service between the old and new service hosting platform and the internet assigned numbers authority (IANA) without breaking the integrity of the DNSSEC trust chain during the key rollover, DS and NS record changes, data update and other stages.To improve the availability of domain name system services, the key points of the platform migration operation were analyzed in detail, and the migration mechanism that can ensure business continuity during the migration process were proposed.